Utilization of milkfish bone flour (chanos Chanos forskal) as complementary health Foods - Fuad Husain Akba; Muhtadin Salam; Andi Ilham Latunra; Eddyman W Ferial; Arif Rahman; Ika Fikriah; Lilies Anggarwati Astuti; Ahmad Shakani Abdullah; Siti Sairah Saireen (JOURNAL OF PHARMACEUTICAL NEGATIVE RESULTS, 2022)
Background: Milkfish (Chanos chanos, Forskal) is one of the strategic commodities to fulfill protein needs that are relatively inexpensive and favored by consumers in Indonesia. The use of milkfish bones (solid waste) is a natural source of Ca for food and supplements. This research is a strategy to maximize the utilization of milkfish resources while effectively reducing waste from the fishing industry. Objectives to find out the content of milkfish bone extract as a complementary health foods. Methods: Experimental laboratory design with a post test only with control group design, this research was conducted at the Biopharmaca Laboratory of the Faculty of Pharmacy, Hasanuddin University. Sampling was done using convenience sampling method. The location of sampling and research in the milkfish aquaculture Barru Regency South Celebes, Pharmacy Laboratory of Alauddin State Islamic University of Makassar and Makassar Health Laboratory Center. Determination of the mineral and vitamin contents of milkfish uses three stages of analysis namely mineral analysis and vitamin analysis. Result: The results of the analysis of milkfish bone extract it was found that the milkfish bone extract the highest content in calcium with a content as many as 4820,06 µg/g and the highest content in milkfish bone flour were found in calcium with a content as many as 76752,55 µg/g. Conclusion: Milkfish bone extract and milkfish bone flour positively contain minerals and vitamins that can be used as complementary health foods.